A Descriptive Study On Teaching Reading ComprehensionIn The Second Year Of SMP N 1 Polanharjo - Mahardinata, Achmatika Putra (2012)
This research paper is intended to describe a descriptive study on teaching reading comprehension in the second year of SMP N 1 Polanharjo. Natural Approach method adopted to teach reading is to enable students in being active in practicing English language. The present curriculum has been based on teaching reading, where the students are expected to master not only one skill, but all skills of English namely listening, reading, speaking and writing. Those skills must be one package of teaching. So, the four language skills have been taught in integrative way. The writer focuses the English teaching-learning process on the second year student. The purpose of this research is to know the implementation of teaching reading comprehension in the second year of SMP N 1 Polanharjo. The data are taken from all elements of teaching-learning process committed by the teacher and the students and other sources such as books, students worksheet, hand lesson. The method of collecting data is descriptive method by employing interview, documentation and observation. This research is descriptive qualitative which does not include any calculation or statistic procedure. The result of the research is the implementation of teaching reading is divided into two main sections; (1) Teacher activity consists of all preparations of the teacher in teaching reading, and (2) The elements of reading course. The problems of teaching reading are about the less of the materials that can influence teaching learning process. Vocabulary or unfamiliar words and the level of difficulty of reading skills cause boring to the students in joining reading activity. Based on the data the portion of teaching reading is enough because the reading activity will be integrated with other English skills.